Persepsi mahasiswa Program Studi Ilmu Perpustakaan dan Informasi Islam IAIN Tulungagung terhadap pemanfaatan telematika dan penerapan e-learning sebagai penunjang kegiatan belajar mengajar di masa pandemi Covid-19 - Arin Prajawinanti; Annisa Dwi Yanti (Faculty of Communication, Padjadjaran University, 2021)
The use of telecommunication, media, and informatics technologies in teaching and learning activities has now been implemented, yet it has not been optimally carried out. Covid-19 pandemic has forced teaching and learning activities to use online system also known as e-learning where online lectures are remotely carried out using telematics. Current e-learning practices are considered to be merely providing lecture materials and paying less attention to the characteristics of its users. Moreover, in reality every e-learning user or student has different abilities in how to manage information. The method used in this research was quantitative with literature review, and the sample in this study were students of Library and Islamic Information Science from IAIN Tulungagung. The problems investigated in this study were (1) How students perceive the implementation of e-learning, and (2) What obstacles occurred during the e-learning process. The result of this research is that through e-learning, the study program of Library and Islamic Information Science at IAIN Tulungaggung can minimize crowds in campus environment. However, in practice, there were still many students who were not prepared to optimally use telematics media and e-learning. Students require good adaptations to be able to undergo e-learning because it will affect the implementation of an effective learning process. There were several obstacles faced by students, particularly related to internet data and networks as well as the ability to understand the delivered materials. Thus, students' perception of e-learning becomes very essential since it may influence their willingness and attitude in performing and utilizing online learning. In this case, lecturers also have an important role in providing interactive and fascinating learning materials in order to improve students’ motivation and enthusiasm so that they may actively participate in virtual learning.